Aero acoustic processes in case of sudden depressurization of a vessel with gas overpressure - Доник, В.Д.; Запорожець, О.І. (Proceedings of National Aviation University (archive), 2006)
Gas pressure oscillation distribution velocity in the two adjacent compartments during an unexpected gas pressure change in one of the compartments. Noise measurement results were given depending on the compartment length downstream membrane.